Optimization of the photoelastic conoscopic fringe pattern processing for the stress measurement on uniaxial PWO crystal cut parallel to the a-c plane and with variable thickness. (1st February 2022) - Natali, P.P.; Cherubini, F.; Davì, F.; Montalto, L.; Rinaldi, D.
Abstract: This paper presents a case study in which conoscopic, non-invasive, photoelastic techniques and the associated model are applied for the first time to investigate the internal stress state of the PbWO4 (PWO) uniaxial crystal, cut normal to the crystallographic a - c plane and with non-uniform thickness. As a matter of facts indeed, in the mass production of crystals it is rather probable to have specimen of non-constant thickness. In addition, the crystal cut, normal to the a - c plane, lead to a complex fringes structure and modeling. This can affect the fringe patterns interpretation, and in turn the interpretation of the stress state within the sample. In this paper we analyze the dependence of some model parameters on the thickness, and the relative interpretation of the fringe pattern in order to obtain a reliable measure of the stress for observations normal to the a - c plane. This procedure can speed up the crystal analysis whatever the thickness of the crystal is.